Mathematical modeling for drug delivery and inflammation process: An application in macular edema - Gonçalves, M. B.; Gudiño, E.; Maia, M.; Oishi, C. M. [UNESP] (Elsevier, 2023)
In this paper, we introduce a mathematical model for the drug release from an intravitreal implant and the subsequent effect of the drug on the inflammation process of macular edema. Coupling the drug transport problem with the growth of the edema, we compare the numerical simulations with patient-specific medical images. We fit the model with respect to one parameter and match the retinal thickness observed in the patient. After the validation of the proposed model, we perform numerical experiments regarding patient-specific treatments. In particular, we analyze the drug concentration in the different sub-domains (e.g., the implant and the retina) and simulate the scenario of edema recurrence and implant re-injection. The proposed mathematical model has the potential to provide important insights into the use of intravitreal dexamethasone implants and the treatment of macular edema.
Keywords: Biodegradable implant; Drug delivery; Implcit-Explicit schemes; non-Fickian diffusion